Journey into genetics: taking the twists and turns of life - Rosli, Rozita (Universiti Putra Malaysia Press, 2015)
Genetics play a major role in our lives and for the most part, we take it for granted. By definition, it is a study of heredity or how the characteristics of living things and their variations are transmitted from one generation to the next. Although genetics has a pervasive influence in every sphere of life, the focus of my research is on human and medical genetics. Almost every human trait and disease has a genetic component, whether inherited or influenced by behavioural factors such as exercise and diet. These genetic components can also modify the body’s response to environmental factors such as toxins or even drugs. Understanding the underlying concepts of human genetics, especially the role of genes, is important for applying genetic and genomic information as well as technologies in healthcare. It is also important in improving disease diagnosis and treatment. The completion of the first mapping of the Human Genome Project has opened tremendous potential for research in which genes relate to human conditions, diseases, impairment and susceptibilities. Hence, the knowledge generated through human genetics research has the potential to improve individual and community health. The following sections will first provide some information about basic genetic concepts, the major types of genetic disease, and the impact of genetic variation. Subsequently, the selected research projects that were carried out in the application of genetics and genetic technologies in cancer, especially breast cancer, infectious diseases and therapeutics, including genetic immunisation will be chronicled and highlighted. It is highly likely that human genetics research through the years will become an increasingly more integral component of medical research. It is hoped that the scope of genetic research illustrated by the current activities in my laboratory reflects this reality.